Hubris and Its Impact on Captain Ahab of Herman Melville’s Moby-Dick - Jarjanazi, Abdo Ibrahim (Al-Adab Journal, 2019)
Hubristic characters, in Greek mythology and in later eras, have been looked at negatively. Once a hubristic character emerges, that would provoke nemesis. Consequently, society would punish him/her since she/he allegedly challenges the gods, ignoring warnings and laws of society, and that would present him/her as someone rude and challenging the norms. Accordingly, such a hubristic character would eventually face moral, spiritual, and physical downfall. However, it seems that presenting a hubristic character in Greek mythology and in later eras in such a negative way is a mere fallacy. In fact, effective pride springs from certainty and over-confidence. Consequently, in demonizing effectively proud characters, they unconsciously impede and restrict human abilities and passions from unleashing against the negatively effective forces of external nature and internal human one, which need great toil to endure. This paper attempts to, first, explore and study the actions and psyche of the proud Captain Ahab of Herman Melville’s Moby-Dick. Its second objective is to study the importance of pride and its great effects on the psyche and behavior of the above mentioned hero and on astonishingly shaping the whole course of evolution of incidents. Third, it aims at showing the noble human passions and abilities propelled by his effective pride where he employs them against the forces of nature. Fourth, it also aims at showing his individuality against the forces of nature and how his effective pride mediates in his inner impulses as an organizer, pushing them forward rather than backward. Accordingly, his pride emerges as an effective force challenging the forces of nature. Captain Ahab appears proud of his abilities and passions. In other words, he well recognizes that he is determined, courageous, daring, fearless, and tenacious. Finally, it concludes that effectively pushing pride foregrounds the captain as extremely effective, influential, and inspiring. He prides himself on the positive attributes which he has, and this eventually makes him infinitely and imperiously assertive, insistent, and equivalent to the forces of external nature where he becomes, in spite of his death, not only a hero but also an inspiring one.